STRATEGI BERSAING PERUSAHAAN DAN KINERJA PERUSAHAAN - Wibowo, Seto Sulaksono Adi; Handayani, Yosi; Lestari, Ade Rika (Riset Akuntansi dan Keuangan Indonesia, 2017)
This research sets out to examine about effect of (1) ratio SG&A/Sales on company performance (2) ratio Sales/CoGS on company performance in which variable ratio of SG&A/Sales and Sales/CoGS used to measure generic strategy of product differentiation strategy. Population in this research is manufacturing sector company from 2012 - 2014 as many as 120 samples. This research is using purposive sampling technique to collect samples. The analysis tool used is simple regression with coefficient determination and t statistic. The results of this research concludes that generic strategy of product differentiation strategy as measured by variable SG&A/Sales and Sales/CoGS effect on company performance as measured by net profit margin (NPM).The limitations of this research are: (1) This research is confined to manufacturing sector companies (2) On average in the annual report and financial statement companies provide information about the complete lack of research and development costs. Recommendation in this research include: (1) For future researcher should take samples of all sectors listed in Indonesia Stock Exchange (2) Adding other variables relating to generic strategies and performance ofÂ  company. Â Keywords: generic strategy, company performance, product differentiation strategy, cost leadership strategy, net profit margin, manufacturing sector company.